(untitled) (Nigerian Journal of Technology, 2015)
In this study, design of experiment (DOE) for response surface methodology (RSM) was used to analyse and optimise the simultaneous effect of solid substrate loading, initial pH and inoculum density on citric acid production from banana peels via solid state fermentation using Aspergillus niger. A three-variable, three-level Box-Behnken design was used to develop a statistical model to describe the relationship between citric acid concentration and the chosen independent variables and to optimise the production of citric acid using RSM. The model was statistically significant (p<0.0001) with a low standard deviation (0.43) and did not show lack of fit (R2=0.999). Citric acid production was significant at high levels of solid loading, low levels of pH and intermediate levels of inoculum density. Solid loading positively influenced citric acid production while the reverse was the case for initial pH. The optimum values of solid loading, pH and inoculum density were 20 g/L, 8 and 4.97×106 spores/mL respectively. Under these conditions, the citric acid concentration was obtained as 49.9 g/L. Validation of the statistical model showed an insignificant difference between experimental and model predicted results. http://dx.doi.org/10.4314/njt.v34i4.8